A needle arthroscopy approach to the temporomandibular joints in dogs - Arzi, Boaz; Goldschmidt, Stephanie; Chrostek, Emilia; Duong, Minh Vo; Filliquist, Barbro; Chou, Po-Yen (Frontiers in Veterinary Science, 2026)
The temporomandibular joint (TMJ) has been identified as an important contributor to orofacial pain and dysfunction in dogs. Although TMJ disorders have been partially characterized, a more comprehensive understanding and development of diagnostic and therapeutic options are needed. Arthroscopy of the TMJ is a technique that allows for direct visualization and inspection of the internal joint structures, in addition to the collection of biopsies and the performance of select surgical procedures under the operator’s direct visual control. This Methods article, illustrated by two clinical cases, demonstrates the practical and efficient use of needle arthroscopy in dogs’ TMJs. Understanding the fundamental aspects of TMJ arthroscopy is important for diagnosing and treating TMJ conditions, especially given the TMJ’s unique anatomical features in dogs. A semi-open approach was found to be more practical and less likely to cause iatrogenic damage than a single stab incision. The ability to visualize joint structures in health and disease and to perform arthroscopy-guided biopsies is valuable and carries clinically relevant implications.